Sexting and Sexual Behavior, 2011–2015: A Critical Review and Meta‐Analysis of a Growing Literature. Issue 3 (15th May 2017) - Kosenko, Kami; Luurs, Geoffrey; Binder, Andrew R.
Abstract: Sexting and its potential links to sexual behavior, including risky sexual practices, have received scholarly scrutiny, but this literature is marked by divergent perspectives and disparate findings. To assess claims regarding the nature of the relationship between sexting and sexual behavior, we conducted a critical review of the literature and analyzed data from 15 articles via quantitative meta‐analytic techniques. Sexting behavior was positively related to sexual activity, unprotected sex, and one's number of sexual partners, but the relationship was weak to moderate. Additional information, gleaned from a critical review of included studies, helped contextualize these findings and point to specific limitations and directions for future research.